Modeling and optimization strategies for improving human resource management effectiveness in private elementary schools: the role of personality, organizational climate, achievement motivation, and knowledge management - Mei Tri Listari; Soewarto Hardhienata; Dian Wulandari (Indonesian Institute for Counseling, Education and Theraphy, 2026)
This study aims to (1) examine the direct effects of personality, organizational climate, and achievement motivation on HRM effectiveness; (2) investigate the mediating role of achievement motivation and knowledge management; and (3) develop optimization strategies using the SITOREM approach. A mixed-methods design combining exploratory qualitative and quantitative causal approaches (POP-SDM method) was employed. Data were collected from 144 principals and teachers in private elementary schools with